A survey and future vision of double auctions-based autonomous cloud service negotiations - Adnan, M.H. (2019)
Double auction-based mechanisms have gained considerable attention as autonomous cloud service negotiation because it has been proven to be economically efficient and possesses the ability to accommodate multiple buyers and sellers. The main objective of this paper was to outline the limitations of the practically tested double auction mechanisms in cloud service negotiations; and subsequently suggest future vision. Ten practically proven double auction-based mechanisms have been surveyed from the research database, whereby most of them were found to employ the double auction protocol and two variations of the double auction protocol, namely continuous double auction and combinatorial double auction. Comparisons on the types, objectives, parameters, and results between the selected mechanisms are presented in this paper. Moreover, it was identified that the surveyed double auction mechanisms were unable to address multi-attributes heterogeneous cloud services because it required a long execution time. Nevertheless, future vision managed to be suggested to solve these issues. Â© Springer Nature Switzerland AG 2019.